SAME-LEVEL FALLS IN OLDER ADULTS: FACTORS ASSOCIATED WITH TRAUMATIC BRAIN AND SPINAL CORD INJURIES - Josy Anne Silva; Gustavo Henrique Marques Moreno; Liliana Yukie Hayakawa; Kelly Cristina Inoue; Roberto Kenji Nakamura Cuman (Universidade Federal do Paraná, 2018)
Objective: to identify factors associated with the occurrence of traumatic brain and spinal cord injuries among older adults who suffered a same-level fall. Method: a retrospective study, with 192 medical records of older adults that suffered a same-level fall in 2014 and were attended in the Emergency Care Unit of a teaching hospital in Paraná. The Z test was performed to compare the proportions of the groups with (n=80) and without (n=112) traumatic brain or spinal cord injuries with demographic, health, fall and evaluation/care data. Results: 80 (41.7%) of the older adults identified had traumatic brain or spinal cord injuries. There was a significant association of the occurrence of traumatic brain or spinal cord injuries with: male gender (p=0.0109), specialized transport (p=0.0001), fall on public road (p=0.0026), absence of arterial hypertension p=0.0434) and presence of psychiatric illness (p=0.0048). Conclusion: traumatic brain and spinal cord injuries are frequent events associated with same-level falls, which indicates the need for educational and preventive measures aimed at the reduction of falls.